September 17-19, 1968 Tokyo, Japan (Tokyo, 1969)
The world today is in a process of great social, economic, and cultural changes. Such changes are marked especially in South and East Asia where many countries have achieved independence since World War II. Population is increasing sharply and its migration to cites is being accelerated, industrial development aimed at rapid economic growth is being pushed, and agricultural productivity is rising.
Keywords: Rural development